Effect of the Duration of Membership in the GATT/WTO on Human Development in Developed and Developing Countries - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2022)
The present article has examined the effect of the duration of the membership in the General Agreement on Tariffs and Trade (GATT) and/or the World Trade Organization (WTO) (and not the mere membership in the GATT/WTO) on human development, considered as a measure of citizens' welfare. The theoretical hypothesis underpinning the analysis is that by fostering export product upgrading, the duration of the membership in the GATT/WTO would reduce economic growth volatility, and consequently promotes human development. The analysis has relied on a panel dataset of 148 developed and developing countries, over the period from 1990 to 2019. It has provided support for the theoretical hypothesis by showing that the membership duration fosters human development in countries that enjoy a high level of export product upgrading, measured through export product diversification, the quality of export products, and the level of economic complexity. Countries with low levels of export product upgrading experience no significant effect of the membership duration on the growth of human development. Interestingly, the membership duration is associated with a higher growth of human development regardless of countries' degree of economic growth volatility. However, the lower the level of economic growth volatility, the larger is the magnitude of the positive effect of the membership duration on the growth of human development. Finally, there exists an heterogenous effect of the membership duration on the growth rate of human development across countries in the full sample, reflecting the degree of stringency of countries' accession procedures to the GATT/WTO.
Keywords: F13; F14; O15; 330; Duration of the membership in the GATT/WTO; Human development; Export product upgrading; Economic growth volatility